Five negative symptom domains are differentially associated with resting state amplitude of low frequency fluctuations in Schizophrenia. (March 2023) - Cheon, Eun-jin; Male, Alie G.; Gao, Bingchen; Adhikari, Bhim M.; Edmond, Jesse T.; Hare, Stephanie M.; Belger, Aysenil; Potkin, Steven G.; Bustillo, Juan R.; Mathalon, Daniel H.; Ford, Judith M.; Lim, Kelvin O.; et al.
Highlights: Frontal and temporal lobe ALFF is associated with negative symptoms severity in schizophrenia. Regional ALFF is differentially associated with negative symptom domains in schizophrenia. Understanding underlying neuropathology of negative symptoms may aid its unmet therapeutic need. Abstract: This study examined associations between resting-state amplitude of low frequency fluctuations (ALFF) and negative symptoms represented by total scores, second-order dimension (motivation and pleasure, expressivity), and first-order domain (anhedonia, avolition, asociality, alogia, blunted affect) factor scores in schizophrenia ( n = 57). Total negative symptom scores showed positive associations with ALFF in temporal and frontal brain regions. Negative symptom domain scores showed predominantly stronger associations with regional ALFF compared to total scores, suggesting domain scores may better map to neural signatures than total scores. Improving our understanding of the neuropathology underlying negative symptoms may aid in addressing this unmet therapeutic need in schizophrenia.